2019
DOI: 10.3389/fimmu.2019.01882
|View full text |Cite
|
Sign up to set email alerts
|

An Immunological Stairway to Severe Tissue Complication Assembly in Bothrops atrox Snakebites

Abstract: Snakebites are a serious public health problem and, in the Amazon, the Bothrops atrox snake is the most frequent cause of envenomation. B. atrox venom (BaV) causes pathophysiological changes with intense, local inflammatory processes, such as severe tissue complication (STC). However, mechanisms associated with the inflammatory process in humans are still poorly understood. Thus, in this study, we sought to describe the profile of local and systemic immunological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 53 publications
4
22
0
1
Order By: Relevance
“…In addition, decreased concentrations of TNF and IFN-γ were observed. These findings demonstrate a high chemotactic and inflammatory response to exposure to venom in patients and corroborate data previously described in B. atrox snakebites, which shows a plasma increase in inflammatory mediators CXCL-8, CCL-5, CXCL-9, CCL-2, CXCL10, IL-6, TNF-α, IL-1β, and IL-10 ( 27 ). We observed in our study a low production of INF-γ, which could be associated with the main cell type producing this molecule (NK cells).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, decreased concentrations of TNF and IFN-γ were observed. These findings demonstrate a high chemotactic and inflammatory response to exposure to venom in patients and corroborate data previously described in B. atrox snakebites, which shows a plasma increase in inflammatory mediators CXCL-8, CCL-5, CXCL-9, CCL-2, CXCL10, IL-6, TNF-α, IL-1β, and IL-10 ( 27 ). We observed in our study a low production of INF-γ, which could be associated with the main cell type producing this molecule (NK cells).…”
Section: Discussionsupporting
confidence: 90%
“…Patients bitten by B. atrox snakes in the Amazonas State, Brazil, presented the installation of a consumption coagulopathy, in which 85% of the patients showed hypofibrinogenemia ( 26 ). In addition, increased levels of soluble inflammatory mediators in patients have been demonstrated, and are associated with increased severity of the accident ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Venom has been detected in blister aspirates collected from the bite site in Bothrops snakebite patients [18,48]. Moreover, local manifestations such as severe edema, blister formation, and necrosis at the bite site have been observed in Bothrops envenomations, which were classified as moderate/severe cases [49]. The most abundant components found in venoms from the B. atrox of Brazilian Amazon are metalloproteinases, c-type lectin-like, phospholipases A 2 and serine proteinases, and are frequently involved in the hemostatic disorders observed in snakebite patients [26,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The coefficient correlation factor was considered significant when p < 0.05. The correlation index (r) was used to categorize the correlation strength as being weak (r ≤ 0.35), moderate (r ≥ 0.36 to r ≤ 0.67), or strong (r ≥ 0.90), as previously described [49,62].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Manaus showed that detection of cell-free nucleic acids may be used to discriminate patients envenomed by Bothrops and healthy controls [ 75 ]. Levels of the inflammatory biomarkers CXCL-9, CXCL-10, IL-6, and IL-10 were higher in Bothrops -envenomed patients when compared to the healthy controls on admission [ 76 ]. Furthermore, there is a number of interactions of CXCL-8, CXCL-9, CCL-2, IL-6, and IFN-γ and fibrinogen levels in patients bitten by viperids, suggesting these cytokines as biomarkers for this type of envenoming [ 77 ].…”
Section: Diagnosis Of Snake Dry Bitesmentioning
confidence: 99%